Development of liquid enhancer for germination and early growth of rice (Oryza sativa L.) under drought stress - Mahadi, Siti Nuratiqah (2019)
Drought affect growth and development of main crops over the world. It has severely affect the yield and quality of rice plant production, including in Malaysia. Recently, rice plantation in Kelantan, Sabah and Terengganu were reported to be in high risk of water scarcity due to the dry and hot weather caused by El Nino phenomena. One of the strategy to alleviate drought stress in plant growth and development is by the application of fertilizer. Therefore, this study aimed to develop liquid enhancer for germination and early growth of rice under drought stress. The first objective was conducted to screen and select low drought tolerant Malaysia Indica rice cultivars. Five rice cultivars produced by MARDI (MR219, MR220, MR263, MR269 and MR284) were germinated in a petri dishes containing 8 ml of distilled water (0 MPa), -0.3 MPa, -0.6 MPa and -1.2 MPa PEG 6000 solution at ± 26°C for ten days. Number of germinated seed, shoot length, root length, fresh weight and dry weight were measured to analyse the germination and early growth performance. The results found that PEG 6000 solution significantly reduced the germination performance and early growth of all rice cultivars in low osmotic potential. The tolerance level of the rice cultivars towards drought can be concluded as follow, MR219 > MR269 > MR263 > MR284 > MR220. MR220 and MR284 were found to be the most sensitive cultivars. The second objective was followed to determine ideal concentration of KCl, TU, Kin, GA3, and SA for germination and early growth of MR220 and MR284 under drought stress. Seed priming and medium supplementation methods were applied. In seed priming method, MR220 and MR284 seeds were primed in KCl (10, 20, 30, 40 mM), TU (10, 20, 30, 40 mM), Kin (0.25, 0.5, 0.75, 1.0 mM), and SA (0.25, 0.5, 0.75, 1.0 mM) for ±16H and germinated in petri dishes containing 8ml of -1.2 Mpa PEG 6000 solution at ± 26°C for ten days. The petri dishes were arranged in complete randomized design (CRD). The findings showed that 10 mM of KCl, 30 mM of TU, 0.25 mM of Kin and 1.0 mM of SA were the ideal concentration for MR220. Meanwhile, 20 mM of KCl, 30 mM of TU, 0.5 mM of Kin and 1.0 mM of SA were the ideal concentration for MR284 for germination and early growth under drought stress. In medium supplementation method, MR220 and MR284 seeds were stressed in -1.2 MPa PEG 6000 (severe drought level) solution for three days and germinated in petri dishes containing KCl (0.5, 1.0, 1.5, 2.0, 10, 20, 30, 40 mM), TU (0.5, 1.0, 1.5, 2.0), GA3 (0.06, 0.12, 0.18, 0.24 mM), and SA (0.25, 0.5, 0.75, 1.0 mM) at ± 26°C for ten days. Based on the results, 1.0 mM of KCl, 2.0 mM of TU, 0.06 mM of GA3 and 1.0 mM of SA were the ideal concentration for drought-stressed MR220. Meanwhile, the ideal concentration for drought-stressed MR284 were shown by 30 mM of KCl, 2.0 mM of TU, 0.12 mM of GA3 and 0.75 mM of SA. The third objective was progressed to determine the best combination treatments of the ideal concentration acquired from the objective two for liquid enhancer development. Similar germination procedure with different liquid enhancer formula was carried out. In seed priming method, the results showed that the best combination treatments for MR220 were 10 mM KCl + 30 mM TU, 10 mM KCl + 1.0 mM SA, and 30 mM TU + 1.0 mM SA. Meanwhile, the best combination treatments for MR284 were 20 mM KCl + 30 mM TU + 0.5 mM Kin + 1.0 mM SA, 20 mM KCl + 30 mM TU + 0.5 mM Kin, and 30 mM TU + 1.0 mM SA. In medium supplementation method, the results showed that the best combination treatments for drought-stressed MR220 were 1.0 mM KCl + 0.06 mM GA3, 0.06 mM GA3 + 1.0 mM SA, and 1.0 mM KCl + 2.0 mM TU + 0.06 mM GA3. Meanwhile, the best combination treatments for droughtstressed MR284 were 30 mM KCl + 0.12 mM GA3, 0.12 mM GA3 + 0.75 mM SA, and 30 mM KCl + 2.0 mM TU + 0.12 mM GA3. The last objective was carried out to evaluate the effectiveness of liquid enhancer in soil medium. This objective was proceeded with medium supplementation method. Drought-stressed MR220 and MR284 were germinated in soil medium for 30 days and supplemented with the liquid enhancer at day 0 and day 15, with 50 ml watered daily. PEG 6000 (-1.2 MPa) was given at 30 ml in alternate day before liquid enhancer treatment to induce drought stress. The best three combination treatments from objective three were used as liquid enhancer treatments. The plant height, root length, biomass, root to shoot ratio, chlorophyll, protein and proline content were measured to analyse the effectiveness of the liquid enhancer on the early growth performance of drought-stressed MR220 and MR284 seedlings. Among the combination treatments tested, combination treatment consist of 1.0 mM KCl + 2.0 mM TU + 0.06 mM of GA3 and 30 mM KCl + 0.12 mM GA3 showed the most effective in improving early growth performance for drought-stressed MR220 and MR284 seedlings respectively. The combination treatments showed 2- fold higher plant height (29.8 cm and 34.3 cm) than control (16.3 cm and 15.7 cm) of drought-stressed MR220 and MR284 respectively. These two combination treatments were found to be the suitable liquid enhancer that able to enhance germination performance and early growth of drought stressed MR220 and MR284.